Chitosan-Based Semen Extenders: An Approach to Antibiotic-Free Artificial Insemination in Rabbit - Francisco Marco-Jiménez; Celia Ferriz-Nuñez; Maria Pilar Viudes-de-Castro; José Salvador Vicente; Laura Lorenzo-Rebenaque (Antibiotics)
Background/Objectives: The use of antibiotics in livestock contributes to antimicrobial resistance, highlighting the need for alternative solutions. Among these, chelating agents, like ethylenediaminetetraacetic acid (EDTA) and Chitosan, have shown potential in reducing bacterial contamination in seminal doses used in artificial insemination (AI), while preserving sperm quality. The objective of this study was to evaluate the potential use of EDTA and Chitosan as alternatives to antibiotics for the liquid storage of rabbit seminal AI doses. Methods: EDTA (20 mM) and Chitosan (0.05%) were tested both individually and in combination, by adding them to the semen extender, and their effects were compared with extenders containing antibiotics or none. The extenders were evaluated for microbial resistance and their ability to maintain sperm quality in vitro during refrigeration at 16 ± 1 °C for 72 h. To assess antimicrobial efficacy, Enterococcus faecalis was used. Seminal doses stored for 24 h were used for insemination under commercial conditions, and fertility rate and total kits born were evaluated. Results: Adding 0.05% Chitosan to the extender resulted in sperm parameters and bacterial load comparable to those achieved with antibiotics during refrigerated storage, yielding similar fertility rate and total kits born outcomes 24 h post-storage. In contrast, the use EDTA alone or in combination with Chitosan was less effective at controlling Enterococcus faecalis than the antibiotic extenders, which also resulted in a reduction of sperm total motility over storage period (0–72 h) and negatively impacted fertility rate and total kits born. Conclusions: Chitosan’s protective effect on sperm function, combined with its antimicrobial activity, makes it a promising alternative antimicrobial agent for the liquid storage of rabbit seminal AI doses.